Elite Schools and Their Social Place: The Bulgarian Case - Milenkova, Valentina; Molhov, Maxim (Calitatea Vieții, 2011)
The present article is focused on a research of school choice under Bulgarian conditions that becomes possible through: – the degree of parents' participation in the decision making; – the students' and parents' expectations for a good start of children and the belief that the given school will secure prosperity; – the readiness of children to follow the choice where parents have a decisive word. All these determinants (of choice) are influenced by students' as well as by parents' opinions and statuses. Bulgarian elite schools are analysed in the present article and a thesis is developed that economic and cultural priorities inherited by families are transformed into school priorities in the education process. Different facets of the elite schools in the years of transition are followed up, and the main accent is put on their students: as social background and environment, achievements, propensity to future education and values, cultural capital. The analysis is based on several surveys carried out by the authors in the period 1996–2005 concerning the Bulgarian elite schools and their social actors. One major conclusion is that the elite school is a response to “social errand” for formation of an elite; these schools support continuity between parents and children, expressing themselves as an institutional mechanism of socialization which is nearest to family aspirations and habitus, representing an investment transmitted within generations.